ANALYSIS OF THE RESULTS OF THE EFFECTIVENESS OF SPECIALIZED PSYCHOLOGICAL ASSISTANCE TO TEENAGERS, WITH REARED WITHOUT THE FAMILY - Oksana Anatolievna Rogozhina (Вестник Северо-Кавказского федерального университета)
In article touched upon the topical problem of the study of personal, behavioural characteristics of adolescents living in a children's home.